Assessment of the feed additive consisting of ammonium propionate for all terrestrial animal species for the renewal of its authorisation (BASF SE, Taminco Finland Oy) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Ammonium propionate is authorised as a liquid preparation of ≥ 19% ammonium propionate, ≤ 80% propionic acid and ≤ 30% water. The applicant requested for the renewal of the authorisation of ammonium propionate when used as a feed additive for all terrestrial animal species. The applicant has provided evidence that the additive in the market complies with the conditions of the authorisation. The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP Panel) confirms that the use of ammonium propionate under the current authorised conditions of use is safe for the target species, the consumers and the environment. Concerning the user safety, the additive is corrosive to skin and eyes. Any exposure is considered a risk. There is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.